1993
DOI: 10.1080/03079459308418909
|View full text |Cite
|
Sign up to set email alerts
|

The use of fenbendazole in the treatment of commercial turkeys infected withAscaridia dissimilis

Abstract: Birds on a commercial turkey Farm were treated with fenbendazole on two separate occasions. For each treatment, fenbendazole was administered in the feed for 3 days at 30 mg/kg. Mean Ascaridia dissimilis total counts in randomly selected birds were 14.4 and 33.0 prior to the first and second treatments, respectively, whilst post-treatment counts averaged only 0.1 and 0.3, respectively. Anthelmintic effectiveness as demonstrated by both treatments was >99.0%. No untoward effects were noted with either fenbendaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 4 publications
0
13
1
Order By: Relevance
“…; Yazwinski et al. , ). Lawrence () showed that a single treatment with fenbendazole eliminated all nematode parasites in 221 of 230 birds from 38 species of six orders.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…; Yazwinski et al. , ). Lawrence () showed that a single treatment with fenbendazole eliminated all nematode parasites in 221 of 230 birds from 38 species of six orders.…”
Section: Methodsmentioning
confidence: 98%
“…In order to minimize the time spent at the nest and thus the invasiveness of the study, we did not attempt to quantify the reduction in parasite levels in relation to the treatment. Yet, several studies have shown that fenbendazole is effective against various intestinal parasites in birds, for example nematodes, lungworms, and cestodes (Norton et al 1991;Yazwinski et al 1992Yazwinski et al , 1993. Lawrence (1983) showed that a single treatment with fenbendazole eliminated all nematode parasites in 221 of 230 birds from 38 species of six orders.…”
Section: Methodsmentioning
confidence: 99%
“…The drug is effective against various intestinal parasites in birds e.g. nematodes, lungworms and cestodes (Norton et al 1991, Yazwinski et al 1992, Yazwinski et al 1993), and may also be effective against acanthocephala as another benzimidazole (albendazole) has been reported to cure acanthocephala infections in monkeys (Weber and Junge 2000). Additionally, no negative side effects of fenbendazole have been shown in domestic ducks (Short et al 1988, Pedersoli et al 1989).…”
Section: Methodsmentioning
confidence: 99%
“…However, another study indicated that ALB can be effective in protection of turkeys against Heterakis gallinarum or flagellated form of Histomonas (Hegngi et al , ). Clinical effectiveness in the treatment of turkeys infected by Ascaridia dissimilis is described for homologous drug fenbendazole (Yazwinski et al , ). Unfortunately, both ALB studies were performed without any knowledge of the pharmacokinetics of ALB and its active metabolite SOX.…”
Section: Introductionmentioning
confidence: 99%